Randomised clinical trial: the DPP‐4 inhibitor, vildagliptin, inhibits gastric accommodation and increases glucagon‐like peptide‐1 plasma levels in healthy volunteers. Issue 8 (3rd March 2019) - Rotondo, Alessandra; Masuy, Imke; Verbeure, Wout; Biesiekierski, Jessica R.; Deloose, Eveline; Tack, Jan
Summary: Background: Dipeptidyl peptidase‐4 (DPP‐4) inactivates glucagon‐like peptide‐1 (GLP‐1). Whether DPP‐4 inhibition affects GLP‐1 metabolism and/or food intake in humans remains unknown. Aims: To evaluate the effect of vildagliptin (DPP‐4 inhibitor) on gastric accommodation and ad libitum food intake in healthy volunteers (HVs) Methods: The effects of acute oral vildagliptin administration (50 mg) were evaluated in two randomised, placebo‐controlled, single‐blinded trials. Protocol 1 (n = 10, 32.3 ± 3 years, 23.4 ± 0.7 kg/m 2 ): 60 min after treatment, a nutrient drink (270 kcal) was infused intragastrically and intragastric pressure (IGP) was measured for 1 h. Protocol 2 (n = 10, 24.3 ± 0.8 years, 22.3 ± 0.9 kg/m 2 ): 60 min after treatment, HVs consumed one nutrient drink (300 kcal). Thirty minutes thereafter, HVs ate ad libitum from a free‐choice buffet for 30 min. Blood was collected at several time points to measure active GLP‐1 plasma levels. Results: During the first 20 min after nutrient infusion, the drop in IGP was smaller after vildagliptin compared to placebo (treatment‐by‐time interaction effect: P = 0.008). No differences were seen on epigastric symptom scores. Planned contrast analysis showed that active GLP‐1 levels were higher after vildagliptin compared to placebo ( P = 0.018) only after nutrient ingestion. Total food intake (316.38 ± 58.89 g vs 399.58 ± 63.02 g, P = 0.359) and total caloric intake (594.77 ± 115.17 kcal vs 742.77 ± 107.10 kcal, P = 0.371) did not differ between treatments. Conclusions: Vildagliptin inhibits gastric accommodation without affecting epigastric symptom scoring in HVs. Active GLP‐1 plasma levels were increased after vildagliptin treatment, but the increase was not sufficient to affect ad libitum food intake. The study was registered at Clincialtrials.gov (NCT 03500900).